K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 7 2024

 Nếu \(n\) chẵn thì đpcm trở thành \(\dfrac{3n+1}{4n-1}\le\dfrac{3n+4}{4n-1}\) \(\Leftrightarrow3n+1\le3n+4\) \(\Leftrightarrow1\le4\), luôn đúng.

 Nếu \(n\) lẻ thì đpcm thành \(\dfrac{3n-1}{4n+1}\le\dfrac{3n+4}{4n-1}\)

 \(\Leftrightarrow\left(3n-1\right)\left(4n-1\right)\le\left(4n+1\right)\left(3n+4\right)\)

 \(\Leftrightarrow12n^2-3n-4n+1\le12n^2+16n+3n+4\)

 \(\Leftrightarrow26n+3\ge0\) (luôn đúng)

 Vậy với mọi \(n\inℕ^∗\) thì \(\dfrac{3n+\left(-1\right)^n}{4n-\left(-1\right)^n}\le\dfrac{3n+4}{4n-1}\)

1. There are 5 homes in a row numbere 1 to 5. Each house is painted a different color and has individuals of different countries, each owning different pets, drinking different beverages, and enjoying different brands of candy. 2. The Englishman lives in the red house. 3. The Spaniard owns the dog. 4. Coffee is drunk in the green house. 5. The Ukrainian drinks tea. 6. The green house is numbered one more than the ivory house. 7. The person who eats M&Ms owns snails. 8. Kit Kats are...
Đọc tiếp

1. There are 5 homes in a row numbere 1 to 5. Each house is painted a different color and has individuals of different countries, each owning different pets, drinking different beverages, and enjoying different brands of candy.

2. The Englishman lives in the red house.

3. The Spaniard owns the dog.

4. Coffee is drunk in the green house.

5. The Ukrainian drinks tea.

6. The green house is numbered one more than the ivory house.

7. The person who eats M&Ms owns snails.

8. Kit Kats are eaten in the yellow house.

9. Milk is drunk in home 3.

10. The Nowregian lives in home 1.

11. The man who eats Cadbury's lives in the house next to the man with the fox.

12. Kit Kats are eaten in the house next to the house where the horse is kept.

13. The Snickers eater also drinks orange juice.

14. The Japanese enjoys Reese's candy.

15. The Norwegian lives next to the blue house.

Now, who drinks water? And who owns the zebra? 

1
4 tháng 7 2024

loading...

=> The Norwegian drinks water. The Japanese owns the zebra.

Câu 3:

\(u_1=\dfrac{2\cdot1+1}{1+2}=\dfrac{3}{3}=1\)

\(u_4=\dfrac{2\cdot4+1}{4+2}=\dfrac{9}{6}=\dfrac{3}{2}\)

\(u_5=\dfrac{2\cdot5+1}{5+2}=\dfrac{11}{7}\)

Câu 2:

\(u_n=u_1+\left(n-1\right)\cdot d\)

=>\(-3\left(n-1\right)+4=-41\)

=>-3(n-1)=-45

=>n-1=15

=>n=16

Câu 1:

Tổng của 50 số hạng đầu là 5150

=>\(\dfrac{n\cdot\left[2\cdot u_1+\left(n-1\right)\cdot d\right]}{2}=5150\)

=>\(\dfrac{50\left(2\cdot5+\left(50-1\right)\cdot d\right)}{2}=5150\)

=>\(25\left(10+49d\right)=5150\)

=>49d+10=206

=>49d=196

=>d=4

\(u_{10}=u_1+9d=5+9\cdot4=5+36=41\)

Câu 1:

-2;x;-18;y là cấp số nhân

=>\(\left\{{}\begin{matrix}x^2=\left(-2\right)\cdot\left(-18\right)\\\left(-18\right)^2=x\cdot y\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x^2=36\\xy=324\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}\left\{{}\begin{matrix}x=6\\y=\dfrac{324}{6}=54\end{matrix}\right.\\\left\{{}\begin{matrix}x=-6\\y=\dfrac{324}{-6}=-54\end{matrix}\right.\end{matrix}\right.\)

=>Chọn C

Câu 2:

\(u_4=u_2\cdot q^2\)

=>\(4q^2=9\)

=>\(q^2=\dfrac{9}{4}=\left(\dfrac{3}{2}\right)^2\)

=>\(\left[{}\begin{matrix}q=\dfrac{3}{2}\\q=-\dfrac{3}{2}\end{matrix}\right.\)

TH1: q=3/2

\(u_2=q\cdot u_1\)

=>\(u_1=\dfrac{u_2}{q}=4:\dfrac{3}{2}=4\cdot\dfrac{2}{3}=\dfrac{8}{3}\)

\(u_5=u_1\cdot q^4=\dfrac{8}{3}\cdot\left(\dfrac{3}{2}\right)^4=\dfrac{8}{3}\cdot\dfrac{81}{16}=\dfrac{27}{2}\)

\(u_8=u_1\cdot q^7=\dfrac{8}{3}\cdot\left(\dfrac{3}{2}\right)^7=\dfrac{2^3}{3}\cdot\dfrac{3^7}{2^7}=\dfrac{3^6}{2^4}=\dfrac{729}{16}\)

TH2: q=-3/2

\(u_1=\dfrac{u_2}{q}=4:\dfrac{-3}{2}=4\cdot\dfrac{-2}{3}=-\dfrac{8}{3}\)

\(u_5=u_1\cdot q^4=-\dfrac{8}{3}\cdot\left(-\dfrac{3}{2}\right)^4=-\dfrac{8}{3}\cdot\dfrac{81}{16}=\dfrac{-27}{2}\)

\(u_8=u_1\cdot q^7=\dfrac{-8}{3}\cdot\left(-\dfrac{3}{2}\right)^7=\dfrac{-2^3}{3}\cdot\dfrac{\left(-3\right)^7}{2^7}=\dfrac{2^3}{3}\cdot\dfrac{3^7}{2^7}=\dfrac{3^4}{2^4}=\dfrac{81}{16}\)

Câu 3:

\(\left\{{}\begin{matrix}u_1+u_5=51\\u_2+u_6=102\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}u_1+u_1\cdot q^4=51\\u_1\cdot q+u_1\cdot q^5=102\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}u_1+u_1\cdot q^4=51\\q\left(u_1+u_1\cdot q^4\right)=102\end{matrix}\right.\Leftrightarrow q=2\)

\(u_1+u_5=51\)

=>\(u_1\left(1+q^4\right)=51\)

=>\(u_1=\dfrac{51}{2^4+1}=\dfrac{51}{17}=3\)

\(u_4=u_1\cdot q^3=3\cdot2^3=24\)

\(u_{12}=u_1\cdot q^{11}=3\cdot2^{11}=6144\)

Câu 1: \(u_4=u_1+3k\)

=>\(3k=\dfrac{3}{8}-3=\dfrac{3}{8}-\dfrac{24}{8}=-\dfrac{21}{8}\)

=>\(k=-\dfrac{7}{8}\)

\(u_7=u_1+6k=3+6\cdot\dfrac{-7}{8}=3-\dfrac{42}{8}=\dfrac{24-42}{8}=-\dfrac{18}{8}=-\dfrac{9}{4}\)

Câu 2: 

\(\dfrac{u_5}{u_8}=8\)

=>\(\dfrac{u_1\cdot q^4}{u_1\cdot q^7}=8\)

=>\(\dfrac{1}{q^3}=8\)

=>\(q=\dfrac{1}{2}\)

\(u_{12}=u_1\cdot q^{11}=12\cdot\left(\dfrac{1}{2}\right)^{11}=\dfrac{12}{2^{11}}=\dfrac{3}{2^9}\)

Câu 3:

Tổng của 5 số hạng đầu là:

\(S_5=\dfrac{u_1\cdot\left(1-q^5\right)}{1-q}=\dfrac{2\cdot\left(1-4^5\right)}{1-4}=682\)

=>Chọn D

Câu 25:

\(0< \alpha< \dfrac{\Omega}{2}\)

=>\(0< sin\alpha< 1;0< cos\alpha< 1\)

 \(\sqrt{\dfrac{1+sin\alpha}{1-sin\alpha}}+\sqrt{\dfrac{1-sin\alpha}{1+sin\alpha}}\)

\(=\sqrt{\dfrac{\left(1+sin\alpha\right)^2}{\left(1-sin\alpha\right)\left(1+sin\alpha\right)}}+\sqrt{\dfrac{\left(1-sin\alpha\right)^2}{\left(1-sin\alpha\right)\left(1+sin\alpha\right)}}\)

\(=\sqrt{\dfrac{\left(1+sin\alpha\right)^2}{cos^2\alpha}}+\sqrt{\dfrac{\left(1-sin\alpha\right)^2}{cos^2\alpha}}\)

\(=\dfrac{1+sin\alpha+1-sin\alpha}{cos\alpha}=\dfrac{2}{cos\alpha}\)

Câu 28:

loading...

loading...

loading...

27 tháng 6 2024

a, \(sin^2x+cos^2x=1\Leftrightarrow cos^2x=1-\dfrac{9}{25}=\dfrac{16}{25}\Leftrightarrow cosx=\dfrac{4}{5}\)

\(tanx=\dfrac{sinx}{cosx}=-\dfrac{3}{5}:\left(\dfrac{4}{5}\right)=-\dfrac{3}{4}\)

\(cotx=-\dfrac{4}{3}\)

c, \(sin^2x+cos^2x=1\Leftrightarrow sin^2x=1-\dfrac{9}{25}=\dfrac{16}{25}\Leftrightarrow sinx=\dfrac{4}{5}\)

\(tanx=\dfrac{sinx}{cosx}=\dfrac{4}{5}:\dfrac{3}{5}=\dfrac{4}{3}\)

\(cotx=\dfrac{3}{4}\)

b, \(cos^2x+sin^2x=1\Leftrightarrow sin^2x=1-\dfrac{1}{16}=\dfrac{15}{16}\Leftrightarrow sinx=\dfrac{\sqrt{15}}{4}\)

\(tanx=\dfrac{\sqrt{15}}{4}:\dfrac{1}{4}=\sqrt{15}\)

\(cotx=\dfrac{1}{\sqrt{15}}\)

d, \(sin^2x+cos^2x=1\Leftrightarrow sin^2x=1-\dfrac{25}{169}=\dfrac{144}{169}\Leftrightarrow sinx=\dfrac{12}{13}\)

\(tanx=\dfrac{12}{13}:\left(-\dfrac{5}{13}\right)=-\dfrac{12}{5}\)

\(cotx=-\dfrac{5}{12}\)

a: \(\Omega< x< \dfrac{3}{2}\Omega\)

=>cosx<0

Ta có: \(sin^2x+cos^2x=1\)

=>\(cos^2x=1-sin^2x=1-\left(\dfrac{3}{5}\right)^2=\dfrac{16}{25}\)

mà cosx<0

nên \(cosx=-\dfrac{4}{5}\)

\(tanx=\dfrac{sinx}{cosx}=\dfrac{-3}{5}:\dfrac{-4}{5}=\dfrac{3}{4}\)

\(cotx=\dfrac{1}{tanx}=\dfrac{4}{3}\)

b: \(0< x< \dfrac{\Omega}{2}\)

=>sin x>0

\(sin^2x+cos^2x=1\)

=>\(sin^2x=1-\left(\dfrac{1}{4}\right)^2=\dfrac{15}{16}\)

mà sin x>0

nên \(sinx=\dfrac{\sqrt{15}}{4}\)

\(tanx=\dfrac{sinx}{cosx}=\dfrac{\sqrt{15}}{4}:\dfrac{1}{4}=\sqrt{15}\)

\(cotx=\dfrac{1}{tanx}=\dfrac{1}{\sqrt{15}}=\dfrac{\sqrt{15}}{15}\)

c: 0<x<90 độ

=>sin x>0

\(sin^2x+cos^2x=1\)

=>\(sin^2x=1-\left(\dfrac{3}{5}\right)^2=\dfrac{16}{25}=\left(\dfrac{4}{5}\right)^2\)

mà sin x>0

nên \(sinx=\dfrac{4}{5}\)

\(tanx=\dfrac{sinx}{cosx}=\dfrac{4}{5}:\dfrac{3}{5}=\dfrac{4}{3}\)

\(cotx=1:\dfrac{4}{3}=\dfrac{3}{4}\)

d: \(180^0< x< 270^0\)

=>sin x<0

\(sin^2x+cos^2x=1\)

=>\(sin^2x=1-\left(-\dfrac{5}{13}\right)^2=1-\dfrac{25}{169}=\dfrac{144}{169}\)

mà sin x<0

nên \(sinx=-\dfrac{12}{13}\)

\(tanx=\dfrac{sinx}{cosx}=\dfrac{-12}{13}:\dfrac{-5}{13}=\dfrac{12}{5}\)

\(cotx=\dfrac{1}{tanx}=\dfrac{5}{12}\)

\(A=2\cdot cos\left(\dfrac{\Omega}{2}+x\right)+sin\left(5\Omega-x\right)+sin\left(\dfrac{3\Omega}{2}+x\right)+cos\left(\dfrac{\Omega}{2}+x\right)\)

\(=3\cdot cos\left(\dfrac{\Omega}{2}+x\right)+sin\left(\Omega-x\right)+sin\left(\dfrac{\Omega}{2}+\Omega+x\right)\)

\(=-3\cdot sinx+sinx+cos\left(\Omega+x\right)\)

\(=-2\cdot sinx-cosx\)

\(B=sin\left(\Omega+x\right)-cos\left(\dfrac{\Omega}{2}+x\right)+cot\left(2\Omega-x\right)+tan\left(\dfrac{2\Omega}{2}+x\right)\)

\(=-sinx+sinx+cot\left(-x\right)+tan\left(x\right)\)

\(=tanx-cotx=tanx-\dfrac{1}{tanx}=\dfrac{tan^2x-1}{tanx}\)

24 tháng 6 2024

Giúp mình với ạ mình cảm ơn